Teaching The Indonesian Language As A Heritage Language For Diaspora Children - Rizki Putri Ramadhani; Fendy Yogha Pratama; Fatah Nasikh Aryawan (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
Indonesian diaspora children have different characteristics compared to foreign students in general. They have acquired Indonesian naturally in their families. This background makes them included in the category of learners of Indonesian as a heritage language. The teaching of Indonesian that is done to them also has special characteristics. Therefore, this study specifically focuses on the characteristics of teaching Indonesian as a heritage language for diaspora children by using a qualitative approach and descriptive analysis. The data obtained through in-depth interviews with three teachers were then codified and analyzed. Based on the results of the analysis, it was found that the teaching in the Indonesian language as a heritage language class for these children has four characteristics. First, the teaching uses the total physical response (TPR) method. Second, it focuses on teaching daily vocabulary. Third, it focuses on teaching daily language skills. Fourth, teaching is assisted by the role of parents. Suggestions and recommendations from the results of this study are intended for Indonesian language teachers and researchers.  Researchers should research more about the role of parents in learning Indonesian for diaspora children in the family. For Indonesian language teachers, it is recommended to focus on teaching daily vocabulary in everyday contexts using the TPR method.Keywords: heritage language, young learners, Indonesian diaspora, Indonesian language teaching